Legal Protection of Outsourced Labor Based on Law No.13 of 2003 in PT Pertamina Trans Continental Port Jakarta - Asmara, Asmara; Nurtresna, Robby; Mabsuti, Mabsuti (SEAN Institute, 2025)
The outsourcing system is regulated legally, but in reality many workers feel disadvantaged and want the outsourcing system to be abolished. In this case, the request for legal protection for workers at PT Pertamina Trans Kontinental Port Jakarta was caused by problems with the outsourcing system at PT Pertamina Marine Solution, the problem is that workers whose outsourcing contracts are regulated to be Effective from January 1 to December 31, but when changing or extending a new contract, it is usually issued or signed by outsourcing workers around March. The new contract has not been issued but workers have started working and their salaries are paid continuously every month. If later a problem arises, how can workers claim insurance when there is no clarity in the outsourcing contract? The problem that occurs is the result of weak legal protection for outsourcing workers. The research method used is empirical with a normative approach. The data sources used are primary data and secondary data. Primary data is data obtained from related parties involved in this study, namely the entrepreneur PT Pertamina Trans Kontinental Port Jakarta, the outsourcing actor PT Pertamina Marine Solution (PMSol) and workers at PT Pertamina Trans Kontinental Port Jakarta. While secondary data is data obtained from literature studies. Based on the results of research on the implementation of legal protection for workers, the implementation of fixed-term work agreements at PT. Pertamina Trans Kontinental Port Jakarta still does not comply with the provisions of laws and regulations, namely, fixed-term work agreements that are not recorded or there is no renewal of worker documents, because the company realizes that the fixed-term work agreement is not in accordance with laws and regulations, weak supervision from the authorities, workers' ignorance of PKWT, workers' lack of courage because they are afraid of being laid off, and workers' apathy. and the legal consequences of fixed-term work agreements that are not recorded or there is no renewal of documents, namely by law they change into PKWTT.